2017
DOI: 10.1186/s13071-017-2182-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel zoonotic Anaplasma species is prevalent in small ruminants: potential public health implications

Abstract: BackgroundTick-borne diseases currently represent an important issue for global health. A number of emerging tick-transmitted microbes continue to be discovered, and some of these are already identified as the cause of human infections. Over the past two decades, Anaplasma phagocytophilum is considered to be mainly responsible for human anaplasmosis. However, a novel zoonotic pathogen provisionally named “Anaplasma capra” has recently been identified in China. In this study, we did an active surveillance of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 18 publications
7
32
0
Order By: Relevance
“…Epidemiological data for this pathogen in wildlife are lacking in Korea; however, our findings are similar to those obtained from wildlife (five takins, three Himalayan gorals, three Reeves's muntjacs, one forest musk deer and one wild boar) in China [24]. In addition, a low percentage of infection rate was reported cattle, sheep and goats in China, Sweden and Korea [15][16][17][18][19], indicating that A. capra has a broad host range. Occurrence of infection during the study period from 2015 to 2018 indicates the persistence of the infection in KWD, suggesting that the species may act as a reservoir for this pathogen.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Epidemiological data for this pathogen in wildlife are lacking in Korea; however, our findings are similar to those obtained from wildlife (five takins, three Himalayan gorals, three Reeves's muntjacs, one forest musk deer and one wild boar) in China [24]. In addition, a low percentage of infection rate was reported cattle, sheep and goats in China, Sweden and Korea [15][16][17][18][19], indicating that A. capra has a broad host range. Occurrence of infection during the study period from 2015 to 2018 indicates the persistence of the infection in KWD, suggesting that the species may act as a reservoir for this pathogen.…”
Section: Discussionsupporting
confidence: 82%
“…Our genetic profiling results indicated that the newly generated 16S rRNA gene sequences shared a homology of > 99.5% with sequences of A. capra strains from humans, sheep, goats, cattle and ticks [12,15,16,18,20,22], suggesting that they likely are within the same species of bacteria [38,39]. Clustering of sequences named A. centrale from deer (Cervus nippon nippon) (GenBank: AB211164) and cattle (GenBank: AF283007) in Japan and from ticks (Haemaphysalis longicornis) in Korea (Gen-Bank: GU064903), as well as Anaplasma spp.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations